Contrasting Granite Metallogeny through the Zircon Record: A Case Study from Myanmar. - Gardiner, Nicholas; Hawkesworth, C.; Robb, L.; Whitehouse, M.; Roberts, N.; Kirkland, C.; Evans, Noreen (Nature Publishing Group, 2017)
Granitoid-hosted mineral deposits are major global sources of a number of economically important metals. The fundamental controls on magma metal fertility are tectonic setting, the nature of source rocks, and magma differentiation. A clearer understanding of these petrogenetic processes has been forged through the accessory mineral zircon, which has considerable potential in metallogenic studies. We present an integrated zircon isotope (U-Pb, Lu-Hf, O) and trace element dataset from the paired Cu-Au (copper) and Sn-W (tin) magmatic belts in Myanmar. Copper arc zircons have juvenile eHf (+7.6 to +11.5) and mantle-like d(18)O (5.2-5.5‰), whereas tin belt zircons have low eHf (-7 to -13) and heavier d(18)O (6.2-7.7‰). Variations in zircon Hf and U/Yb reaffirm that tin belt magmas contain greater crustal contributions than copper arc rocks. Links between whole-rock Rb/Sr and zircon Eu/Eu* highlight that the latter can monitor magma fractionation in these systems. Zircon Ce/Ce* and Eu/Eu* are sensitive to redox and fractionation respectively, and here are used to evaluate zircon sensitivity to the metallogenic affinity of their host rock. Critical contents of Sn in granitic magmas, which may be required for the development of economic tin deposits, are marked by zircon Eu/Eu* values of ca. =0.08.